Genetic Evaluation of 269 Rice Landraces for Grain Quality and Blast Resistance Genes - Tong, Thi Thuy Trang; Ngo, Thi Phuong Du; Tran , In Do; Pham, An Tinh; Nguyen, Pham Ngoc Diep; Bui, Nguyen Ngoc Dung; Pham, Thi Be Tu; Huynh, Ky (Hue University Journal of Science: Natural Science, 2025)
The overuse of agrochemicals has intensified the focus on breeding rice varieties with enhanced grain quality and resistance to major diseases. This study aimed to evaluate genetic variation related to grain quality and blast resistance in landrace rice varieties using gene-specific molecular markers. Five target genes, including Wx, BADH2, GS3, Pi54, and Pi-ta, were analyzed for their association with key traits. Among the accessions, 52 carried the Wx allele associated with low amylose content, 14 possessed the aromatic BADH2 allele, and 99 carried the mutant GS3 allele associated with long grain. For blast resistance, 17 genotypes harbored Pi54 and 97 carried Pi-ta, both major resistance genes. The research highlights valuable allelic diversity for use in marker-assisted selection and the development of elite rice cultivars with improved grain quality and disease resistance.